Load-dependent increase in lumbar kyphosis is associated with posterior pelvic tilt during deadlift - Shoji, Kazuma; Nakayama, Koichi; Shiouchi, Masayo; Manabe, Yoshiaki (Frontiers in Sports and Active Living, 2025)
IntroductionAlthough numerous previous studies have examined how different loading weights affect lumbar intervertebral discs during deadlift, the specific characteristics of trunk movement during these lifts remain unclear. This study aimed to compare how varying load weights affect trunk motion during deadlift, utilizing a model that accounts for the trunk's multi-degree-of-freedom motion.MethodsThirteen participants performed standard deadlift at 60%, 70%, 80%, and 90% of their one repetition maximum (1RM). Reflective markers were placed on specific anatomical landmarks, including the tips of six spinous processes, and measured using an optical motion capture system. We then constructed a six-region link segment model of the trunk to calculate kinematic data for each spinal region in the sagittal plane. These data were subsequently compared across the different load weights.ResultsThe lower thoracic and upper lumbar regions showed increased flexion angle displacements as load weight increased. Additionally, the pelvis's posterior tilt accelerated with heavier loads.DiscussionWhile flexing the lumbar spine during lifting can be an effective strategy for successfully completing high-load deadlift, it may increase stress on the lumbar intervertebral discs. Therefore, maintaining lumbar spine lordosis and anterior pelvic tilt while ensuring trunk rigidity is important during high-load deadlift.